Anterior cruciate ligament resection has no clinical effect on mediolateral gap laxity assessment in robotic-assisted total knee arthroplasty - Filippo Leggieri; Samuel Grant; Jil A. Wood; Natasha Sergis; Gregory C. Wernecke; Darren B. Chen; Samuel J. MacDessi (Bone & Joint Open, 2026)
Aims The aim of this investigation was to assess the effects of anterior cruciate ligament (ACL) resection on assessment of mediolateral laxity gaps during robotic-assisted total knee arthroplasty (TKA). Methods We conducted a prospective study on 251 patients undergoing robotic-assisted primary TKA between January and June 2025. Patients with previous ACL or other knee ligament injury, and cases with missing data on outcomes of interest were excluded. Pre-resection mediolateral stressed laxity gaps in extension (10°) and flexion (90°) were measured in millimetres using optical navigation data before and after ACL resection. The primary outcome was paired mean difference in medial and lateral laxity gap measurements. The secondary outcome was prediction of factors associated with gap measurement differences. Paired t -tests with mean differences (MDs) compared pre- and post-resection measurements, with multivariate linear regression models examining independent predictors. Results ACL resection did not alter medial extension gaps (MD 0.0 mm, p = 0.317) and lateral extension gaps (MD 0.1 mm, p = 0.172). Clinically negligible but statistically significant changes in medial flexion (MD 0.1 mm, p = 0.001) and lateral flexion gaps (MD 0.2 mm, p < 0.001) were noted, with all below the established minimum clinically important difference threshold of 0.3 mm. Multivariate regression identified mechanical hip-knee-ankle angle and medial posterior tibial slope as significant predictors for lateral extension gap differences ( β 0.05, p < 0.001 and β –0.04, 95% CI 0.06 to –0.01, p = 0.006, respectively). Conclusion These findings indicate that routine ACL sacrifice is not necessary when evaluating extension and flexion gap measurements used for functional positioning in robotic-assisted TKA. Cite this article: Bone Jt Open 2026;7(8):1118–1125.